The extent of the social worker’s use of group discussion technique in professional practice with school activity groups in Tubas Governorate schools (Journal Of Educational and Psychological Researches, 2022)
This study aimed at identifying the extent to which the social worker used the techniques of group discussion in the professional practice with the groups of school activity in the schools of Tubas governorate in light of some variables (gender, years of experience, academic qualification). The analytical descriptive method was used due to its suitability for the objectives of the study.  A questionnaire was designed to collect data that included (30) items, distributed in three areas .The validity and reliability of the tool were verified and then distributed to the study sample. The results of the study showed that the highest averages were in the discussion stage domain, where the pre-discussion stage was medium and the lowest averages were in the post-discussion stage.